Kajian Normatif Yuridis Terhadap Peran Lembaga Arbitrase Syariah Dalam Penyelesaian Sengketa Perbankan Syariah - W, Wahidin; Zahro, Fifin Anisatu; Ainun, Nur; Zilarsi, Inda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the function of sharia arbitration institutions as an alternative solution for resolving disputes in sharia banking activities in Indonesia. The approach employed is a juridical normative approach, analyzing legal regulations, fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and relevant references in the field of sharia economic law. The findings of this study indicate that sharia arbitration, particularly through the National Sharia Arbitration Board (BASYARNAS), plays a crucial role in providing legal certainty and resolving disputes in accordance with sharia provisions. The existence of this institution provides an alternative to litigation, which is often lengthy and does not always reflect sharia justice. However, the effectiveness of sharia arbitration institutions still faces several obstacles, such as low public understanding of the arbitration process, limited resources, and the implementation of arbitration decisions at the execution level. Therefore, strengthening regulations, education, and collaboration between Islamic banking, judicial institutions, and Islamic arbitration institutions is crucial to creating an efficient, fair, and sharia-compliant dispute resolution system.